Morphogenesis of galls induced by Baccharopelma dracunculifoliae (Hemiptera: Psyllidae) on Baccharis dracunculifolia (Asteraceae) leaves - Arduin,M. (2005)
The commonest insect gall on Baccharis dracunculifolia (Asteraceae) leaves is induced by Baccharopelma dracunculifoliae (Hemiptera, Psyllidae). The gall-inducing insect attacks young leaves in both the unfolded and the fully expanded stages. Four developmental phases were observed in this type of gall: 1) A folding phase, during which the leaf lamina folded upward alongside the midrib and the edges of the upper portion of the leaf approached each other, forming a longitudinal slit. A single chamber was formed on the adaxial surface of the leaf; 2) A swelling phase, in which the folded leaf tissues thickened and the edges of the leaf drew closer together, narrowing the slit. In this phase the gall matured, turning succulent, fusiform and pale green. The single nymphal chamber was lined with white wax and was able to house from one to several nymphs; 3) A dehiscence phase, characterized by the opening of the slit to release inducers; and 4) A senescence phase, when the gall turned dark and dry. The dermal system of the mature gall was composed of a single-layered epidermis. The mesophyll was swollen, and the swelling was due mainly to hyperplasia of the parenchyma. The vascular tissues along the midrib vein were conspicuous and the perivascular fibers resembled parenchymal cells. The hypertrophied secretory cavities contained low lipophylic content. This gall does not form nutritive tissue, but salivary sheaths left by the inducers were observed near the parenchyma, vascular bundles and secretory cavities. This study complements our current knowledge of gall biology and sheds further light on the plasticity of plant tissues stimulated by biotic factors.